Effect of high- and low- frequency transcutaneous electrical nerve stimulation (TENS) on angiogenesis and wound contraction in acute excisional wounds in rat skin - Aline Fernanda Perez Machado; Fabio Leite Silva; Marco Aurélio Invaldi Neves; Fábio Luis Nonato; Pascale Mutti Tacani; Richard Eloin Liebano (Fisioterapia em Movimento)
Abstract Introduction: Transcutaneous electrical nerve stimulation (TENS) can alter the local temperature, increase skin blood flow and induce the release of vasodilator neuropeptides and growth factors. These changes may be related to the effects of TENS on the tissue repair process. Objective: To assess the effect of high- and low-frequency TENS on angiogenesis and the contraction of acute excisional wounds in rat skin. Methods: Fifty-four young adult male EPM1-Wistar rats were used in the study. An excisional wound was performed on the back of each animal using an 8mm punch. The animals were randomly assigned to three groups: the High-frequency Group (HG: 80 Hz), Low-frequency Group (LG: 5 Hz), and Sham Group (SG: TENS turned off). TENS was delivered on three days consecutives. Pulse duration and current intensity were 200 µs and 15 mA. The length of each TENS session was 60 minutes. Microscopic and macroscopic assessments were performed on 3, 7 and 14 postoperative (PO) days. Hematoxylin-eosin staining was utilized to quantify the neoformed blood vessels. Photographs were taken to determine the percentage of wound contraction. After assessment, the animals were painlessly sacrificed. Results: There were increases in angiogenesis in the HG on the 3 PO day, and in the LG on the 14 PO day. No significant differences in wound contraction were found between the groups on the different PO days. Conclusion: High frequency TENS improved angiogenesis, and neither frequency of TENS had any influence on the contraction of acute excisional wounds in rat skin.